Grafting phenolics onto milk protein via conjugated polymerization for delivery of multiple functionalities: Synthesis and characterization. (15th December 2019) - El-Maksoud, Ahmed A. Abd; Anankanbil, Sampson; Zhou, Ye; El-Ghany, Ismail H. Abd; El-Beltagi, Hossam S.; Banerjee, Chiranjib; Petersen, Steen V.; Guo, Zheng
Highlights: β-Lactoglobulin (βLg) was functionalized with polymeric units containing caffeic acid (βLg-polyCA). Products were characterized by NMR, MALDI-TOF MS & FTIR, DSC and CD analysis. βLg-polyCA presented the highest antioxidant and free radical-scavenging activity. TBARS demonstrated βLg-polyCA affording up 4–5 fold of oxidative rancidity inhibition compared to native βLg. Compared to native βLg, βLg-polyCA displayed a drastic secondary structure change. Abstract: A synthetic scenario for functionalization of β-lactoglobulin (βLg) with polymeric units containing caffeic acid (βLg-polyCA) was developed; and all intermediates and final products were structurally confirmed using nuclear magnetic resonance spectroscopy, matrix assisted laser desorption ionization time-of-flight mass spectrometry, and physico-chemically characterized using differential scanning calorimetry and circular dichroism. The antioxidant properties and emulsion stability of βLg, βLg-CA conjugate and βLg-polyCA based systems containing high percentage of fish oil (50%) were evaluated; and βLg-polyCA presented the highest antioxidant and free radical-scavenging activity based on DPPH, ABTS and HS scavenging assays (92.4, 87.92 and 67.35% respectively). Thiobarbituric acid (TBARS) test demonstrated that compared to native βLg, βLg-polyCA afford up 4–5 fold of inhibition of oxidative rancidity and displayed drastic secondary structure changes. Compared to native βLg based emulsions, βLg-polyCA had larger oil droplet sizes, stronger negative zeta potentials (−69.9 mv), narrower size distributions (PDI: 0.22) and less creaming index.